1972
DOI: 10.1021/ac60314a010
|View full text |Cite
|
Sign up to set email alerts
|

Separation of high-boiling petroleum distillates using gradient elution through dual-packed (silica gel-alumina gel) adsorption columns

Abstract: Sodium nitrite is not quantitatively reduced under the present experimental conditions, since alkaline reduction of nitrates and nitrites with iron(II) are quantitative only in 28% sodium hydroxide (17) and lower alkali concentration requires silver or copper catalyst (18).Interferences. The use of iron(II) in acidic and alkaline media for reduction of nitro and nitroso groups has the advantage over titanium(III), since very little interference is (16) F. Feigl, "Spot Tests in Organic Analysis," Elsevier, Amst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Following convention for gradient elution chromatography (Hirsch et al, 1972;Snyder et al, 1979;Radke et al, 1980;Jandera and Churácek, 1985), ASE columns were sequentially eluted with solvent of increasing eluotropic strength (ε 0 ; Meyer and Palamareva, 1993) to separate the TLE into fractions based on unsaturation and polarity. Less conventionally, ASE columns were inverted to reverse solvent flow and back elute more polar compounds.…”
Section: Compound Separation: Solvent Elution Schedulementioning
confidence: 99%
“…Following convention for gradient elution chromatography (Hirsch et al, 1972;Snyder et al, 1979;Radke et al, 1980;Jandera and Churácek, 1985), ASE columns were sequentially eluted with solvent of increasing eluotropic strength (ε 0 ; Meyer and Palamareva, 1993) to separate the TLE into fractions based on unsaturation and polarity. Less conventionally, ASE columns were inverted to reverse solvent flow and back elute more polar compounds.…”
Section: Compound Separation: Solvent Elution Schedulementioning
confidence: 99%
“…Fractionation of maltenes was carried out on a silica/alumina column chromatography. [43][44][45][46] An open glass column of 2 3 60 cm 2 were packed with neutral alumina (200-300 mesh) in its lower half and silica gel (200-300 mesh) in its upper half. Silica gel was washed with toluene/dichloromethane/methanol (1:1:3, v/v) mixture and then dried.…”
Section: Sara Fraction Analysismentioning
confidence: 99%
“…ASTM D 2007 (Clay-gel Analysis) and a technique developed by Hirsch et al 18 are column chromatographic procedures used to separate high-boiling petroleum fractions into saturated, aromatic, and polar compounds. Barman 19 showed that ASTM D 2007 is subject to cross-contamination of these hydrocarbon classes.…”
Section: Hydrocarbon Type Analysismentioning
confidence: 99%